Non-Invasive Capnography Versus Pulse Oximetry for Early Detection of Respiratory Depression During Pediatric Procedural Sedation: A Prospective Observational Study - Laura Català Altarriba; Sean Yeh Hsi; Aude Marie Ravit; Sònia Brió Sanagustín; Xoan González-Rioja (Children, 2025)
Background/Objectives: Continuous ventilation monitoring during pediatric sedation is essential, as respiratory depression may occur silently and may not be detected promptly by conventional methods such as pulse oximetry. Non-invasive capnography has been proposed to improve early detection of respiratory compromise. This prospective observational study evaluated the diagnostic accuracy of non-invasive capnography, compared to pulse oximetry, for detecting respiratory depression in pediatric patients undergoing sedation. Methods: We conducted a single-center, prospective observational study at a tertiary pediatric hospital, enrolling 101 patients (ages 1–17 years) undergoing sedation for diagnostic or therapeutic procedures. Patients were monitored using both pulse oximetry and non-invasive capnography. Episodes of respiratory depression—defined as apnea, hypopneic hypoventilation, bradypneic hypoventilation, and desaturation—were recorded. We compared the diagnostic performance and time to detection between capnography and pulse oximetry. Results: We identified 93 episodes of respiratory depression in 52 patients (51.1%). Capnography detected all apnea episodes and 76.9% of hypopneic hypoventilation episodes that were not identified by pulse oximetry. The median time advantage of capnography over pulse oximetry was 35 s (p = 0.0055). Combining capnography and pulse oximetry identified more events than pulse oximetry alone (93 vs. 53 episodes). Conclusions: Non-invasive capnography improves the early detection of respiratory depression compared to conventional monitoring with pulse oximetry in pediatric procedural sedation. While these findings support its routine use to enhance patient safety, larger multicenter studies are needed to demonstrate its diagnostic accuracy and impact on clinical outcomes.